iGPI and PGPI: national-scale cooperative R&D rollout of IAM planning methods and tools - Coelho, S. T. (2015)
The National Iniciative for Infrastructure Asset Management (iGPI) led by LNEC, IST and Addition, and its twin initiative PGPI, led by AGS, were collaborative projects through wich a total of 30 Portuguese water utilities developed IAM systems and plans through a collective trainnig, capacitation and R&D rollout programme (Apr 2012 - Oct 2013). The utilities received specialized training, collective and individual sipport, and networked with the other utilities in a commom process with similar difficulties and challenges, leading to an effective sharing of solutions. The products, including software, training materials, guidelines and templates for developing strategic and tactical IAM plans, are in the public domain. The projects have significantly contributed to the rollout of reference methodologies and standards for IAM planning, demonstrated in a range of utilities of varied size and context, successfully pushing a consensual best pratice. The methodology and outcomes are discussed and illustrated with selected cases.